NTRK Fusion in Non-Small Cell Lung Cancer: Diagnosis, Therapy, and TRK Inhibitor Resistance - Liu, Fangfang; Wei, Yuxuan; Zhang, Huan; Jiang, Jizong; Zhang, Peng; Chu, Qian (Frontiers in Oncology, 2022)
Neurotrophic tropomyosin receptor kinase (NTRK) gene fusion has been identified as an oncogenic driver of various solid tumors, and it is rare in non-small cell lung cancer (NSCLC) with a frequency of approximately less than 1%. Next-generation sequencing (NGS) is of priority for detecting NTRK fusions, especially RNA-based NGS. Currently, the tropomyosin receptor kinase (TRK) inhibitors have shown promising efficacy and well tolerance in patients with NTRK fusions-positive solid tumors, regardless of tumor histology. The first-generation TRK inhibitors (larotrectinib and entrectinib) are recommended as the first-line treatment for NSCLC patients with positive NTRK fusion. However, TRK inhibitor resistance can eventually occur due to on-target or off-target mechanisms. Further studies are under investigation to overcome resistance and improve survival. Interestingly, NTRK fusion might be the mechanism of resistance to epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitors (TKI) in NSCLC patients with EGFR mutation. Regarding to immunotherapy, the efficacy of immune checkpoint inhibitors in NSCLC patients harboring NTRK fusion has yet to be well described. In this review, we elucidate the function of NTRK genes, summarize the diagnostic techniques for NTRK fusions and present clinical data for TRK inhibitors, we also discuss potential mechanisms of resistance to TRK inhibitors.